2005
DOI: 10.4103/0253-7613.16216
|View full text |Cite
|
Sign up to set email alerts
|

Antihepatotoxic effect of grape seed oil in rat

Abstract: The GSO contains 75% linoleic acid, 15% oleic acid, 6% palmitic acid, 3% stearic acid, and 1% linolenic acid. [1] Studies revealed the beneficial HDL effect of GSO and research shows that subjects were instructed to use up to 45 ml of GSO in their daily diet as a substitute for their usual oil and within 2 weeks there was 13-14% increase in HDL level. [2] The GSO has a very high level of antioxidant vitamin E (60-120 mg/100 g), which makes the oil very stable. The antioxidant property is claimed to be the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 8 publications
(4 reference statements)
4
27
0
4
Order By: Relevance
“…GSO is a good source of important bioactive components such as phenolics and antioxidants, which decrease oxidative stress that contributes to the hepatotoxicity [9]. These results agree with Maheswari and Rao, (2005) [42], who found significant decreased in MDA and significant improvement in liver glutathione, superoxide dismutase by oral administration of GSO for 7 days. Also, Ismail et al, (2015) [44], reported that the GSO act as a potent antioxidant its act to scavenge the free radicals, improve the antioxidant and suppress the inflammatory responses enzymes activity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…GSO is a good source of important bioactive components such as phenolics and antioxidants, which decrease oxidative stress that contributes to the hepatotoxicity [9]. These results agree with Maheswari and Rao, (2005) [42], who found significant decreased in MDA and significant improvement in liver glutathione, superoxide dismutase by oral administration of GSO for 7 days. Also, Ismail et al, (2015) [44], reported that the GSO act as a potent antioxidant its act to scavenge the free radicals, improve the antioxidant and suppress the inflammatory responses enzymes activity.…”
Section: Discussionsupporting
confidence: 77%
“…The GSO reduced liver enzymes because its antioxidant properties. Several studies suggested the grape seed oil has hepatoprotective properties as the study of Maheswari and Rao, (2005) [42], who reported that the GSO decreased liver enzymes. Also, the results of the study of Khudair and Aldabaj, (2015) [43], found that the oral administration of GSO with sodium fluoride water showed significant reduction in serum AST and ALP.…”
Section: Discussionmentioning
confidence: 99%
“…Maheswari et al reported that grape seed oil acts protective against hazardous effect of carbon tetrachloride (CCl4) in liver cells. They showed that this is due to antioxidant activity of high vitamin E composition of grape seed oil [35].…”
Section: Resultsmentioning
confidence: 99%
“…orally by stomach tube) and the third group was treated with grape seeds oil (4 ml/kg b.w. orally by stomach tube) according to Maheswari and Rao (2005). Food and water was provided ad-libtum.…”
Section: Experimental Rats Designmentioning
confidence: 99%